2022
DOI: 10.1186/s13005-022-00308-3
|View full text |Cite
|
Sign up to set email alerts
|

A CBCT based analysis of the correlation between volumetric morphology of the frontal sinuses and the facial growth pattern in caucasian subjects. A cross-sectional study

Abstract: Background The aim of this study was to evaluate the relationship between frontal sinus shape and facial growth pattern. Methods The three-dimensional examination was carried out by means of 80 CBCT scans selected from a sample of 1247 records of patients treated, for different reason, at the Department of Biomedical Surgical and Dental Sciences at University of Milan, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico Milan. The sample (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…The average size and volume of the frontal sinus before orthodontic treatment were 45.8 ± 12.3 mm in breadth, 29.8 ± 7.3 mm in height, 22.7 ± 5.1 mm in depth, and 5151.6 ± 2711.4 mm 2 in volume. These values were nearly consistent with those of previous studies [ 8 , 9 , 17 ]. Furthermore, no age-related differences in the frontal sinus size and volume were found in the present study, similar to previous studies [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The average size and volume of the frontal sinus before orthodontic treatment were 45.8 ± 12.3 mm in breadth, 29.8 ± 7.3 mm in height, 22.7 ± 5.1 mm in depth, and 5151.6 ± 2711.4 mm 2 in volume. These values were nearly consistent with those of previous studies [ 8 , 9 , 17 ]. Furthermore, no age-related differences in the frontal sinus size and volume were found in the present study, similar to previous studies [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…These values were nearly consistent with those of previous studies [ 8 , 9 , 17 ]. Furthermore, no age-related differences in the frontal sinus size and volume were found in the present study, similar to previous studies [ 8 , 9 ]. Using radiographic examination of the frontal sinus, Brown et al [ 18 ] reported that the main expansion of the sinus ceased at the age of 15.68 years in males and 13.72 years in females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The authors [14,15] reported a low percentage (0.16%) of cases of incidental findings of a foreign body, but they emphasized the importance for the orthodontist to carefully analyze the pre-orthodontic treatment radiographs not only from an orthodontic point of view. In specific cases such as craniofacial malformations, impacted teeth, etc., a three-dimensional imaging technique such as cone beam computed tomography (CBCT) is needed [16][17][18]. Some research studies have shown that incidental findings observed in CBCT scans can report a frequency of up to 92% [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding angle between these two longitudinal axes is defined as the crown to root angle and therefore, the CA is the supplementary angle of the crown to root angulation, used to correlate the angular difference between the two axes [ 3 ]. The CA of single rooted teeth is crucial in the field of dentistry especially orthodontics, prosthodontics, periodontics and implantology since a variation in CA might affect the prognosis of many dental treatments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%